Understanding the global decline in the labor income share - Saumik Paul (IZA World of Labor, 2020)
Globally, the share of income going to labor (the “labor income share”) is declining. However, this aggregate decline hides more than it reveals. While the labor income share has decreased for low-skilled workers, this has been concurrent with an increase for high-skilled workers. Globalization leading to a growing skill premium and an increasing complementarity between capital and skill through the advancement of technology explains the polarization of labor income shares across the skill spectrum.
Keywords: E24; E25; J30; 330; labor income share; skills; technology; globalization